(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:At the forefront of the research, the two researchers discussed its importance in the training of goalkeepers in futsal football, by introducing aids in the training process that contribute to preparing them in exercises according to visual thinking, and knowing the impact of these exercises on some of the skills of goalkeepers in futsal football, which would raise the level of goalkeeper efficiency. As for the problem of the research, the two researchers found the importance of training goalkeepers in futsal football by setting some skills and tests for goalkeepers in futsal, and by observing a discrepancy in the level of skillful performance of goalkeepers, who attributes the skillful performance of goalkeepers in futsal football due to lack of interest in the visual thinking aspect and speed Observing them, as well as not using the necessary tools allocated in the training units, which would raise the motivation of goalkeepers to continue and perform with more motivation, the most important of which are (symbols, pictures, .......) and therefore these tools serve goalkeepers in terms of thinking and performance in a way general . The two researchers studied all the factors surrounding the players and paid attention to the skill side, and for this we see in recent periods an increase in interest in visual thinking from the modern methods that can be relied upon to improve skills, as goalkeepers rely on visions, ideas and images that enter into mental processes and translate them into actions or methods of play Which increases the goalkeeper’s self-confidence and their ability to read the opposing attacker when trying to score. And since futsal is one of the games that has received and continues to receive great attention from different countries because it is one of the sports that is characterized by its wide popularity and is special in having elements of excitement and suspense, and it is the result of football and this interest made specialists always seek to develop the game by raising The levels of the players in terms of skill, and therefore it was necessary to pay attention to the number of new exercises commensurate with the game and its requirements that need to perform skills at a high level, due to the narrowness of the playing areas and their small size, and because they require accuracy and speed in the movement of the goalkeeper for futsal with high concentration, and that the development of the capabilities of goalkeepers It depends on the extent of their interaction with the coach and their response to him. There is no doubt that the coach always works to improve the capabilities of the goalkeepers and work to raise their physical and skill level. It has the tactical numbers, and the mastery of the basic skills comes through various exercises and continuous training for a long period of time for the purpose of mastering and fixing them to reach the best level. Hence the importance of research in working on preparing exercises according to visual thinking commensurate with the skills of goalkeepers to work on raising self-confidence and improving the skills of goalkeepers in futsal football.The study aimed to1- Preparing exercises according to the visual thinking of soccer goalkeepers for futsal.2- Knowing the effect of exercises on some soccer goalkeeper skills for futsal.As for the research hypotheses- There are significant differences between the results of the pre-tests and the results of the post-tests for some goalkeeper skills in futsal football, in favor of the post-tests of the sample under study.The researchers also touched on several researches related to auxiliary training means to learn about the basic skills and qualities needed by the goalkeeper, and some models of previous studies similar to the research were presented to benefit from them.A number of conclusions were reached, most notably:The researchers used special exercises within the visual thinking that I used in the main experiment to have a positive effect on the skillful performance of the short handling by hand and the short handling by the foot of the skills of goalkeepers in football for futsal players, as the results showed a clear superiority of the experimental group in the post-test over the pre-test.In light of the conclusions reached by the researchers, the following is recommended:1- Working on benefiting from the results of the current study by using special exercises (visual thinking networks) in training and giving it great importance during the training units in the period of special preparation for futsal goalkeepers, because of its importance in developing the intellectual aspect and perceptions of futsal goalkeepers .2- Paying attention to diversifying the means and tools used in the training unit together, and working to make them compatible with the requirements of football goalkeepers for futsal.Keywords: exercises, visual thinking, goalkeeper skills in futsal football.